Soykırım Suçunun Değerlendirilmesi ve Uluslararası Hukukta “Çifte Standartlar” Sorunu - Allahyarova, Tahire (Fırat University, 2013)
Soykırım kurbanlarının sayısı milyonlarca olsa da, bugün bu suçun cezalandırılmasını amaçlayan uluslararası uygulamada sadece bir-iki olgu mevcuttur. Yitirilmiş insan yaşamları, zamanla kıyaslandığında ona siyasi ve hukuki değer verilmesinde mutabakatın olmaması, insanlık için iyi olan hiçbir şey vaadetmiyor. Soykırıma uluslararası birliğin değer vermesi için öncelikle onun planlanmış politika olduğunun vurgulanması, ona “çifte standartlar” prizmasından yaklaşımın yerilmesi ve bu yönde bir tek uluslararası cepheden bakılması sadece Azerbaycan için değil, genel olarak dünya için en gerekli meselelerdendir.

Although the number of victims of the genocide are in millions today, there are only a few cases have been reported that aims to be punished for this crime in international practice. Lost people lives and the lack of consensus granting political and legal value to this issue that compared to time period does not promise anything good for humanity. In order to provide value to the genocide by international association, it is completely essential not only for Azerbaijan, but also for world in general to emphasize that its planned policy, there are “double standards” approach through to this issue and it should be evaluated only by International Union
Evaluation of the Crime of Genocide and “Double Standards” Issue in the International Law